2004
DOI: 10.1111/j.1344-3941.2004.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre‐slaughter nutritional condition on intramuscular collagen solubility, pyridinoline cross‐links and meat tenderness in aged goats

Abstract: Effects of preslaughter nutritional condition on intramuscular collagen characteristics were studied, in order to clarify the potential of intensive feeding to aged animals in improving meat tenderness. Ten castrated male goats were assigned into one of two groups: one group was allowed ad libitum access to a concentrate diet (total digestible nutrients 70%, crude protein 15%) and Italian ryegrass hay (ADLIB‐group), and the other group was fed a restricted amount of their diet (concentrate diet 0.5% of bodywei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Meat tenderness is determined by its structure, condition and chemical composition. To make meat tender, it must be left to age suffi ciently to allow rigor mortis to loosen up [Shiba et al, 2004].…”
Section: Evaluation Of Technological Parametersmentioning
confidence: 99%
“…Meat tenderness is determined by its structure, condition and chemical composition. To make meat tender, it must be left to age suffi ciently to allow rigor mortis to loosen up [Shiba et al, 2004].…”
Section: Evaluation Of Technological Parametersmentioning
confidence: 99%
“…The data presented here suggested that the fat underwent lipid oxidation at a pronounced rate during the first 24 days of storage .The decrease PV observed with extended storage time was presumed to be due to the decomposition of hydro-peroxide, the hydroperoxide formed might undergo decomposition to form secondary lipid oxidation products 18 . The lipid oxidation occurred in Altay sheep fat rapidly during refrigerated storage, might due to the high content of fat and pro-oxidants in fat 19,20 reported that the peroxide value of sardine muscle increased until 9 days reached the maximum value and decreased thereafter during 15 days of iced storage. Changes in TBARS of Altay sheep tail fat during refrigerated storage are also shown in Fig.…”
Section: Changes In Pv and Tbarsmentioning
confidence: 99%
“…In addition, women suffering from PMS experience more stressful situations than healthy people [19,20]. It has also been reported that women with severe PMDD or PMS have a higher anxiety level than those with mild PMS or no PMS [21]. It has been shown that 31% of women with PMS have behavioral disorders [22], of which 25% have anxiety disorder [23,24].…”
mentioning
confidence: 99%